Exploring Javanese as a first language in children’s social groups in Blitar - Rusmawati, Roosi; Khasanah, Ismatul; Mauliddian, Khilmi (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2024)
This study aims to explore the use of Javanese language in the domain of children’s social groups in the Mataraman Area of the Blitar border. Qualitative method is utilized in this study to provide a comprehensive conception of the linguistic phenomenon accurately without any treatment given to the subject matter. As a sociolinguistic study, it aims to observe the language attitude observed in the domain of children’s social groups in the border areas. In an effort to prevent the COVID-19 pandemic, the data was collected by a field team consisting of local residents to expedite the process while still adhering to the established health protocols. It is expected that this study can facilitate policy makers in fostering and maintaining Javanese language as the mother tongue of communities located in cultural border areas. Additionally, the current study can also be utilized as input for preserving and protecting Javanese language as children’s mother tongue as the next generation of native speakers of a certain community in an effort to maintain the identity of their local culture. The results show that there is indeed a shift in language use, i.e., the use of mixed languages—a combination of Javanese Ngoko and Indonesian or a unique mix of Javanese Ngoko, Indonesian, and Malay—as observed in a conversation among siblings when they played together. There are also three major factors that are seen to influence this shift, i.e., parental, technological, and social environmental factors, where these three contribute to children’s interactions.